Modellgestützte Analyse neuer Stromtarife für Haushalte unter Berücksichtigung bedarfsorientierter Versorgungssicherheitsniveaus - Hayn, Marian (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2016)
The central elements of this work are the design of an electricity tariff with variable capacity prices accepted by residential customers and the question how this tariff affects demand flexibility. Therefore, a corresponding tariff concept is developed. Based on an empirical study its acceptance and specific design is analyzed. The impact of different electricity tariffs on demand flexibility is analyzed with a developed bottom-up model for residential load profiles.